Measurement of Radiation Dose Received by the Eye Lens in Panoramic Examination Using a Thermoluminisence Dosimeter (TLD) in the Radiology Installation of Andalas University Hospital - Nisa, Chairun; Hanifah, Wahdini; Nansih, Livia Ade; M.Biomed; Artitin, Cicillia; Fitria, Ananta Della (MSJ : Majority Science Journal, 2026)
A panoramic examination is an examination used to show the upper and lower jaws along with abnormalities in the oral area. The lens of the eye is a sensitive organ that is exposed to radiation during a panoramic examination. The lens of the eye that is exposed to radiation for a long time can cause cataracts that can develop to blindness, therefore to prevent cataracts, BAPETEN No. 6 of 2010 sets a deterministic threshold limit for the chance of cataracts at 15 mSv per year. This study aims to determine how much dose the lens of the eye receives during a panoramic examination and whether the dose received exceeds the established NBD. This type of research is an experimental quantitative study conducted at the Radiology Installation of Andalas University Hospital in September 2025 using a sample of 7 patients. The instruments and materials used are a panoramic machine, TLD and plaster isolation. Dose measurement is done by attaching the TLD to the patient's right and left eyelids then exposed using 73 kV, 10 mA and 10.8 s and then the TLD reading process is carried out. The measurement results obtained in nC units with the final result in the form of an effective dose compared with BAPETEN regulation No. 6 of 2010. The highest effective dose measurement result received by patient 2 was 0.13 mSv and the lowest in patient 1 was 0.095 mSv with an average dose received by all patients of 0.11 mSv. Based on BAPETEN regulation No. 6 of 2010, the deterministic threshold for the chance of cataracts is 15 mSv per year, so the range of effective dose values received by the patient is still within safe limits.